A semi-supervised federated learning approach leveraging pseudo-labeling for Knee Osteoarthritis severity detection - Rifat, Rakib Hossain (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Science in Computer Science, 2024.